Felbamate for pediatric epilepsy—should we keep on using it as the last resort? - Rabinowicz, Shira; Schreiber, Tal; Heimer, Gali; Bar-Yosef, Omer; Nissenkorn, Andreea; E, Zohar-Dayan; Arkush, Leo; Hamed, Nasrin; Ben-Zeev, Bruria; Tzadok, Michal (Frontiers in Neurology, 2022)
Introduction Concerns regarding felbamate adverse effects restrict its widespread use in children with drug-resistant epilepsy. We aimed to examine the efficacy and safety of felbamate in those children and identify the ones who may benefit most from its use. Methods We retrospectively reviewed the medical files of all patients who were treated with felbamate in a tertiary pediatric epilepsy clinic between 2009–2021. Drug efficacy was determined at the first 3 months of treatment and thereafter. Therapeutic response and adverse reactions were monitored throughout the course of treatment. Results Our study included 75 children (age 8.9 ± 3.7 years), of whom 53 were treated with felbamate for seizures, 16 for electrical status epilepticus during sleep and 6 for both. The median follow-up time was 16 months (range 1–129 months). The most common cause for epilepsy was genetic (29%). The median number of previous anti-seizure medications was six [4–8]. A therapeutic response ≥50% was documented in 37 (51%) patients, and a complete response in 9 (12%). Nineteen patients (25%) sustained adverse reactions, including three cases of elevated liver enzymes and one case of neutropenia with normal bone marrow aspiration. In all cases, treatment could be continued. All children with intractable epilepsy following herpes encephalitis showed a response to felbamate. Conclusion Felbamate is an efficacious and safe anti-seizure medication in the pediatric population.